The utility of single fiber EMG in facial nerve paralysis - DATE, Kazuhiro (OTOLOGIA FUKUOKA, 1994)
The utility of single fiber EMG (SFEMG) of the orbicularis oris muscle in facial nerve paralysis was studied in 10 normal human subjects and 12 patients with facial nerve paralysis. In addition, the jitter values of SFEMG were obtained in an animal model, and then the results of the studies were compared. The statistical rejection ellipses of humans and a cat model showed very similar patterns, and the more severe the facial damage, the greater the deviation from the rejection ellipse range. Furthermore, as the recovery proceeded, the coordinates of the jitter values gradually approached each other and finally came into the normal range. The jitter values of SFEMG and stimulated SFEMG in an animal model showed similar patterns during the recovery phase of facial nerve paralysis. We thus conclude that follow-up study of the jitter values of SFEMG and stimulated SFEMG in patients with facial nerve paralysis can offer valuable information that is useful and relevant to their treatment.